2018
DOI: 10.1136/rmdopen-2018-000714
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and treatment of new-onset arthritis after checkpoint inhibitor therapy

Abstract: Immune checkpoint inhibitors (ICIs) may cause immune-related adverse events (IRAEs). Characterisation and data on treatment of musculoskeletal IRAEs are scarce. In this cohort study, patients receiving ICI therapy who experienced arthralgia were evaluated for the presence of synovitis. Data on demographics, ICI regime, time of onset, imaging and response to therapy of synovitis were prospectively collected. Arthritis was demonstrated in 14 of 16 patients of whom 7 showed monarthritis, 5 had oligoarthritis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 21 publications
2
74
0
2
Order By: Relevance
“…In another study, the SE allele HLA DRB1*01:01 was found in two out of nine patients who had inflammatory arthritis after treatment with an ICI; however, comparison to a control population was not reported . Interestingly, several studies have shown that SpA‐associated HLA‐B27 alleles do not appear to confer increased risk for ICI‐IA, as almost all patients who developed ICI‐IA were HLA‐B27‐negative . The genetic studies performed thus far show that SE alleles, but not HLA‐B27 alleles, associate with ICI‐IA.…”
Section: Geneticsmentioning
confidence: 97%
See 4 more Smart Citations
“…In another study, the SE allele HLA DRB1*01:01 was found in two out of nine patients who had inflammatory arthritis after treatment with an ICI; however, comparison to a control population was not reported . Interestingly, several studies have shown that SpA‐associated HLA‐B27 alleles do not appear to confer increased risk for ICI‐IA, as almost all patients who developed ICI‐IA were HLA‐B27‐negative . The genetic studies performed thus far show that SE alleles, but not HLA‐B27 alleles, associate with ICI‐IA.…”
Section: Geneticsmentioning
confidence: 97%
“…Thus far, most reports are from small case series or single‐center cohort studies and the assays used to detect seropositivity are not uniform between studies. Despite these limitations, aggregation of the data from multiple studies reveals a low rate of seropositivity among patients developing IA following treatment with ICI therapy with 5.5% (12/217; range 0%‐36%) positive for RF and 5% (11/217; range 0%‐11%) positive for ACPAs . In a study comparing ICI‐IA patients to ethnically matched counterparts with RA, 7.7% of ICI‐IA patients were positive for RF or ACPAs, whereas 64.6% of RA patients were positive for ACPAs and 56.7% positive for RF, with 49.3% being positive for both .…”
Section: Serologymentioning
confidence: 99%
See 3 more Smart Citations